Case Report: Three-dimensional printed prosthesis reconstruction for patello-femoral large osteochondral defects in a patient with distal femoral giant cell tumour: A case report - Yuan, Dechao; Fang, Xiang; Lei, Senlin; Banskota, Nishant; Kuang, Fuguo; Gou, Yawei; Zhang, Wenli; Duan, Hong (Frontiers in Bioengineering and Biotechnology, 2022)
Background: The restoration and reconstruction of patello-femoral large osteochondral defects caused by bone tumours are challenging because of the local recurrence rate and the joint’s mechanical complexity. Although three-dimensional (3D)-printed prostheses are commonly adopted for tumour-induced bone defect reconstruction, patello-femoral osteochondral reconstruction with 3D-printed prostheses is rarely reported. Case presentation: A 44-year-old female patient with progressive swelling and pain in the left knee for six months was diagnosed with Campanacci Grade II giant cell tumour (GCT). She underwent intralesional curettage combined with autografting and internal fixation, after which complications of deep infection arose. The patient then underwent internal fixation removal and cement packing. Afterwards, the pain of the affected knee persisted for 11 months, and bone cement removal plus 3D-printed modular prosthesis reconstruction was performed. At the last follow-up 27 months after surgery, she was pain free, the Musculoskeletal Tumour Society (MSTS) score improved from 15/30 to 29/30, the Visual Analogue Scale (VAS) score decreased from 7 to 0, and knee flexion increased from 50º to 130º. X-ray images 22 months after surgery showed that the prosthesis and screws were in a stable position, and callus formation was found at the prosthesis-bone interface. Conclusions: A 3D-printed modular prosthesis may be a useful treatment option for the surgical reconstruction of GCT-induced patello-femoral large osteochondral defects. The firm fixation, osseointegration, and favourable congruency of the 3D-printed prosthesis with the adjacent articular surface can achieve long-term knee function and stability.